Glia-Mediated Regenerative Response Following Acute Excitotoxic Damage in the Postnatal Squamate Retina - Eymann, Julia; Di-Poï, Nicolas (Frontiers in Cell and Developmental Biology, 2020)
The retina is a complex tissue responsible for both detection and primary processing of visual stimuli. Although all vertebrate retinas share a similar, multi-layered organisation, the ability to regenerate individual retinal cells varies tremendously, being extremely limited in mammals and birds when compared to anamniotes such as fish and amphibians. However, little is yet known about damage response and regeneration of retinal tissues in "non-classical" squamate reptiles (lizards, snakes), which occupy a key phylogenetic position within amniotes and exhibit unique regenerative features in many tissues. Here, we address this gap by establishing and characterizing a model of excitotoxic retinal damage in bearded dragon lizard (Pogona vitticeps). We particularly focus on identifying, at the cellular and molecular level, a putative endogenous cellular source for retinal regeneration, as diverse self-repair strategies have been characterized in vertebrates using a variety of retinal injury and transgenic models. Our findings reveal for the first time that squamates hold the potential for postnatal retinal regeneration following acute injury. Although no changes occur in the activity of physiologically active progenitors recently identified at the peripheral retinal margin of bearded dragon, two distinct successive populations of proliferating cells at central retina respond to neurotoxin treatment. Following an initial microglia response, a second source of proliferating cells exhibit common hallmarks of vertebrate Müller glia (MG) activation, including cell cycle re-entry, dedifferentiation into a progenitor-like phenotype, and re-expression of proneural markers. The observed lizard glial responses, although not as substantial as in anamniotes, appear more robust than the absent or neonatal-limited regeneration reported without exogenous stimulation in other amniotes. Altogether, these results help to complete our evolutionary understanding of regenerative potential of the vertebrate retina, and further highlight the major importance of glial cells in retinal regeneration. Furthermore, our work offers a new powerful vertebrate model to elucidate the developmental and evolutionary bases of retinal regeneration within amniotes. Such new understanding of self-repair mechanisms in non-classical species endowed with regenerative properties may help designing therapeutic strategies for vertebrate retinal diseases.